Americas at the millennium : a time of testing : a report (Inter-American Dialogue WashingtonUS, 2000)
Focuses on the failure so far of most democratic governments in Latin America and the Caribbean to satisfy the demands of their citizens for steadier and faster economic growth, accelerated social progress, full political participation, and greater personal security. Argues that democratice politics and market economies are on trial across the region, and are at grave risk in some countries.
Located in the Office of the Secretary General